2018
DOI: 10.11611/yead.360164
|View full text |Cite
|
Sign up to set email alerts
|

Geleceğe Yöneli̇k Tahmi̇nleme Anali̇zi̇: Türki̇ye Çi̇mento Üreti̇mi̇ Uygulamasi

Abstract: Küresel olarak uluslararası ekonomik rekabetin giderek artmasından dolayı bazı sektörlerin rolü giderek artmaktadır. Bu sektörler içinde yer alan çimento sektörü bir ülke için ekonomik büyümenin öncü göstergeleri arasında yer almaktadır. Çimento, ülkemizde yaşanan inşaat sektörü temelli bütün

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
0
0
0
Order By: Relevance
“…According to the research findings, it was observed that the best performance was achieved using the three-period double moving average method. The results also suggest that cement production in Turkey is expected to continue increasing in the coming years (Tüzemen & Yıldız, 2018). In another study examining the significance of Turkey's cement sector and the necessity of strategic approaches for the future, a focus is placed on using economic growth and foreign trade variables to analyze potential developments in the cement sector for the years 2030 and 2050.…”
Section: Literaturementioning
confidence: 99%
See 3 more Smart Citations
“…According to the research findings, it was observed that the best performance was achieved using the three-period double moving average method. The results also suggest that cement production in Turkey is expected to continue increasing in the coming years (Tüzemen & Yıldız, 2018). In another study examining the significance of Turkey's cement sector and the necessity of strategic approaches for the future, a focus is placed on using economic growth and foreign trade variables to analyze potential developments in the cement sector for the years 2030 and 2050.…”
Section: Literaturementioning
confidence: 99%
“…However, by 2020, the production had reached 85 million tons, propelling Turkey to the 5th position in the world rankings. In a relevant study using Double Exponential Smoothing methods, the expectation for the year 2019 was approximately 79.3 million tons (Tüzemen & Yıldız, 2018). However, the actual quantity achieved was even higher.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…The cement industry is primarily a capital-intensive sector; however, the various secondary uses of cement have greatly contributed to the emergence of new business opportunities in countries like Turkey. As a result, during Turkey's development plan periods, governments have provided significant support for the growth of this sector (Tüzemen and Yıldız, 2018).…”
Section: Introductionmentioning
confidence: 99%